Experimental progress on the emergent infinite-layer Ni-based superconductors. (May 2022) - Zhou, Xiaorong; Qin, Peixin; Feng, Zexin; Yan, Han; Wang, Xiaoning; Chen, Hongyu; Meng, Ziang; Liu, Zhiqi
Graphical abstract: Abstract: The emergence of the infinite-layer superconducting nickelate thin films marks the Ni age of superconductivity, which has excited a huge surge of studies since the first report in August of 2019. Despite of the tremendous attention drawn from the entire material science community and a large body of theoretical studies, the experimental progress has been relatively slow due to the challenging sample fabrication, which may, in turn, be holding back the fast development of theoretical research. Therefore, a timely and comprehensive review on all the up-to-date experimental progress of the emergent infinite-layer Ni-based superconductors is urgently needed. In this review, we first introduce the history of more than 30-year-long Ni-based superconductivity exploration, then summarize the sample fabrication processes, later present the experimental electrical transport and magnetic properties, and finally come up with several key issues deserving intensive studies. This review is thus expected to be helpful for researchers with diverse research background to readily capture the major progress of this emerging field.